Pertanggungjawaban Pidana Korporasi dalam Kasus Ilegal Fishing - Siregar, Emiel Salim; Balqis, Raudha; Rahmadani, Fitria; Hasibuan, Adelia Fahriza; Eliyana, Lulu Indah; Sayendra Putri, Dina Natasha (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
This study investigates corporate criminal liability in fisheries crimes, with particular emphasis on illegal fishing as a persistent threat to Indonesia’s marine sustainability, economic stability, and maritime sovereignty. Despite the absence of explicit recognition of corporations as criminal subjects in the Criminal Code, several sectoral regulations—including the Fisheries Law, Emergency Law No. 7 of 1955, and Supreme Court Regulation No. 13 of 2016—have established the basis for holding corporations accountable for offenses committed by their agents. Employing a normative legal approach, this study analyzes statutory frameworks, legal doctrines, and relevant literature to examine regulatory arrangements, sanctioning mechanisms, and enforcement practices. The findings reveal significant legal and institutional challenges, particularly the ambiguity in determining corporate representation in criminal proceedings and the lack of clear standards for attributing corporate fault. Although the Fisheries Law provides cumulative sanctions, including imprisonment, substantial fines, and administrative penalties such as license revocation and asset confiscation, enforcement remains ineffective due to fragmented authority and weak inter-agency coordination. This study argues that strengthening corporate criminal enforcement requires regulatory harmonization, clearer doctrinal standards, and enhanced institutional integration. It further highlights the strategic role of surveillance technologies, such as Vessel Monitoring Systems (VMS), Automatic Identification Systems (AIS), and digital logbooks, in improving compliance and detection. By addressing these gaps, the study contributes to advancing a more coherent and effective framework for corporate accountability in fisheries governance within contemporary criminal law discourse.